Current status and molecular epidemiology of rabies virus from different hosts and regions in Malawi - Henson Kainga; Elisha Chatanga; Marvin Collen Phonera; John Pilate Kothowa; Precious Dzimbiri; Gladson Kamwendo; Malala Mulavu; Cynthia Sipho Khumalo; Katendi Changula; Herman Chambaro; Hayato Harima; Masahiro Kajihara; et al. (Archives of Virology, 2023)
Although rabies is endemic in Malawi, there have been no studies in which rabies virus was systematically investigated and characterized in multiple animal hosts in that country. In order to provide molecular epidemiological data on rabies virus in Malawi, 683 suspected rabies case reports from 2008 to 2021 were examined, and 46 (dog = 40, cow = 5, and cat = 1) viable rabies-positive brain samples archived at the Central Veterinary Laboratory (CVL), Lilongwe, Malawi, were analyzed genetically. The results showed an increase in the submission of brain samples from 2008 to 2010, with the highest number of submissions observed in 2020. Of the 683 case reports analyzed for the period under review, 38.1% (260/683) (CI: 34.44 – 41.84) were confirmed by direct fluorescent antibody test. Among the confirmed cases, 65.4% (170/260) (CI: 59.23 – 71.09) were canine rabies. Further, phylogenetic analysis revealed that sequences from different animal hosts clustered together within the Africa 1b lineage, suggesting that the strains circulating in livestock are similar to those in domestic dogs. This finding supports the hypothesis that canine rabies is spilling over to livestock and emphasizes the need for further studies to provide data for effective control of rabies in Malawi.